Power Electronic Converters for Single-Phase Grid Connected Photovoltaic System: An Overview - Shoro, Ghulam Mustafa; Akbar Hussain, D. M. (International Journal of Integrated Engineering, 2020)
The Solar photovoltaic (PV) power system have achieved meteoric rise through the years. The uptake is not difficult to explain – a drop in cost of PV systems and spiraling electricity cost, have encouraged the end-user to lessen their bills by producing cheaper electricity and can generate revenue by feeding excess power back to the grid. The solar PV is intermittent in nature so it dependent on irradiance and ambient temperature. Power electronics technologies plays an important part for optimizing the energy harvesting from PV system. In order to get maximum extracted power and ensure the load is supplied with a good quality voltage, different dc-dc converters topologies and inverters configurations are used. This paper provides an overview of PV inverter configurations and DC-DC topologies to offer a useful insight and reference point for the researchers working in the field of photovoltaic system.